A compact double‐layer wideband circularly polarized microstrip antenna with parasitic elements. Issue 1 (28th October 2020) - Su, Wei; Li, Junkui; Liu, Ren‐Huai
Abstract: In this article, a new broadband circularly polarized (CP) microstrip patch antenna (MPA) with a sequential phase (SP) square‐loop feeding structure is proposed. The presented antenna is composed of a square‐loop feeding structure, four L‐shaped parasitic patches with L‐shaped slots, four parasitic square patches, and a corner‐truncated square patch. At first, a SP square‐loop is designed as a feeding structure. Then, four L‐shaped parasitic patches with L‐shaped slots are utilized to generate one CP mode by a capacitive coupled way. At last, four parasitic square patches and a corner‐truncated square patch are together placed above the SP feeding structure to broaden the circularly polarized bandwidth (CPBW). The presented antenna has a wide 3‐dB axial ratio bandwidth (ARBW) of 16.7% (5.4 GHz, 4.95‐5.85 GHz), and a wide 10‐dB return loss bandwidth of 25.5% (5.5 GHz, 4.8‐6.2 GHz). The proposed antenna features compact structure and broad 3‐AR bandwidth which could completely cover the WLAN (5.725‐5.85GHz) band. Therefore, the proposed antenna is suitable for circular polarization applications in C band.